Wildfire Intensity and Fire Emissions in Siberia - Evgenii I. Ponomarev; Andrey N. Zabrodin; Eugene G. Shvetsov; Tatiana V. Ponomareva (Fire, 2023)
An analysis of fire characteristics in the boreal forests of Siberia (50–75° N, 60–140° E) was performed for the period 2002–2022. We found a positive trend in the proportion of high-intensity fires in dominant forest stands of Siberia based on long-term series of variations in the Fire Radiative Power (FRP) measurements from the Moderate Resolution Imaging Spectroradiometer (MODIS). Our results showed that there was an increase in the proportion of areas of high-intensity fires over the past decade on about ~30% of the boreal forests of Siberia, including the Arctic zone. For the sample group of fires, the level of correlation (R2 = 0.80–0.94) between the fire impact, classified according to the NBR/dNBR technology, and the integral FRP values was revealed. The intensity of combustion in terms of FRP is associated with the volume of burned biomass and determines the dynamics of specific emissions values per unit area. The results suggest that further increase in fire emissions in Siberia will be determined not only by an increase of burned areas, but also by a redistribution of low- and high-intensity burning and an increase in specific emission values. Finally, we estimated that Siberian fires are responsible for about 5–20% of the total volume of greenhouse gas emissions in the Russian Federation, depending on the fire season scenario. The recurrence of extremely high emissions (296–350 Tg C/year) will make it possible to consider part of Siberian forests as a source of carbon in the nearest future.